Implementation of Smart Biofloc Pond with Solar Cell Powered to Increase the Income Generating of Darul Hikmah Al Hasani Foundation - Sunaryono, Sunaryono; Nandang Mufti; Aripriharta, Aripriharta; Ahmad Taufiq; Ikhwan Najmi; Nadiya Miftachul Chusna (Khidmatuna (Jurnal Pengabdian Kepada Masyarakat), 2023)
The Darul Hikmah Al Hasani Foundation is an elementary Islamic school foundation in Malang City that has an educational tourism learning program about the world of fish. This learning program was stopped due to capital and operational cost constraints. The Malang State University Community Service Team provided a solution in the form of a smart biofloc pond system as another source of income generating for partners which can also be a learning medium for students. The main solution in the smart biofloc pond system is solar cell technology as an alternative energy source for generating electricity to drive water flow so that more oxygen is obtained. This system was chosen because of its various advantages, including greater harvest yields and environmental friendliness due to the optimal use of existing resources in the environment.